Analysis of corporate value statements: an empirical study. (2nd August 2019) - Tessema, Mussie; Dhumal, Parag; Sauers, Daniel; Tewolde, Sebhatleab; Teckle, Paulos
Organisations, whether they are private, public or NGOs have a set of values, whether or not they are written down. This study identifies, classifies, and discusses corporate values statements using companies that are listed on the New York Stock Exchange. The sample companies had 51 value classes, which were then grouped into seven value dimensions: commitment to customers, commitment to stakeholders, commitment to employees, commitment to diversity, commitment to integrity, entrepreneurship, and social responsibility. On the average, they had about six publicised corporate values statements. This study also discusses the theoretical and practical implications of the findings and proposes an agenda for future research directions.